Metropolitan vulnerability and strategic roles for periurban agricultural territories in the context of climate change and variability (2013)
Metropolitan regions are vulnerable to climate change from several perspectives. Their rural territories support many strategic roles essential for the quality of life in these regions, including their contribution to food security. The survival of metropolitan agriculture requires not only protecting agricultural resources. It also requires that the value of the multi-functionality of these agricultural territories be truly appreciated for its contribution to the quality of life in these regions. Finally, farmers also need to further develop their adaptive capacity to different stressors, including climate change and variability, in order to survive and prosper, so that they can continue to play and support these strategic roles in metropolitan regions.